Гельминты реликтовых животных. 1. Aplectana caucasica sp. n. (Nematoda, Cosmocercidae) — паразит кавказской саламандры - Шарпило, В.П. (Вестник зоологии, 1978)
Description, drawings and differential diagnosis of Aplectana caucasica sp. n. from the intestine of Mertensiella caucasica Waga are given in the article. The new species has some distinctive features from A. acuminata (Schrank, 1788) and A. multipapillosa Ivanitzky, 1940 in the shape and size of spicules and gubernaculum, width of lateral wings, egg size, etc.